(untitled) (Journal of Science and Technology, 2015)
The crystallization behaviour of a zinc raw glaze was investigated. In addition to the expected willemite crystals, a new crystal, Zn2TiO308 was identified. This was a gold coloured angular crystal on a blue background of cobalt. It develops on cooling at about 1100°C. This is the first time this crystal is reported in a glaze. In an attempt to make experimental results clearer kinetic reaction, nucleation and crystallization theories and glazing procedures are reviewed in this paper.